EFFECTIVENESS OF WEB BASEDLEARNING TO ENHANCE ANALYTICAL AND PROBLEM SOLVINGSKILLS AT HIGHER SECONDARY LEVEL - et al., P.BAKKIANATHAN (International Journal of Control and Automation, 2019)
World Wide Web (WWW) is expanding limit with regards to sight and sound, multimode correspondence and data introduction, simple access to a regularly developing group of data and better approach for information portrayal, has furnished instructors with energizing chances to improve educating and learning. The examination investigated the viability of Web Based Instruction on the different logical procedure abilities specifically announcing, understanding, thinking and critical thinking aptitudes among higher optional understudies. The Web Based Instruction utilized in the examination targets giving bigger measures of data and creates logical abilities through researching about the subject by the understudies themselves with the assistance of the site.